Corporate value analysis: the moderating role of capital structure - Renata, Virna; Listianingsih, Wahyu; Liza, Maiya (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
Sales have decreased as a result of the slowdown in economic growth, which has impacted profitability in the pharmaceutical subsector. The share values of many pharmaceutical businesses have decreased as a result of this phenomenon during the 2020 pandemic. The research method used is associative quantitative research methodology.The information analyzed comes from the financial statements of companies are listed on the Indonesia Stock Exchange (IDX).Thegoal of this researchisto identify the importance of variations between the variables studied. The sample was chosen by the usepurposive sampling where 8 companies met the criteria for this study. In this investigation, the Moderated Regression Analysis (MRA) technique was used using SPSS version 29. The findings indicated that profitability does not have a significant impact on corporate value, meaning that corporate profits do not affect corporate value. However, liquidity has a significant and positive impact on corporate value, indicating that both profitable and unprofitable corporates have similar corporate value. Capital structure also moderates there lationship between profitability and corporate value, where highly profitable corporates tend to use internal funds, while less profitable corporates rely more on debt. However, capital structure does not moderate the relationship between liquidity and corporate value